Oral Immunization with Recombinant Lactococcus lactis and Retinoic Acid Boost Immune Response in Mice - Nugroho, Inggil Cahyo; Amalia, Maulida Nisa; Juniardi, Muhamad Rizki; Marhendra, Eunike Berliana; Yanma, Nadifa Almira; Adianingsih, Oktavia Rahayu; Winarsih, Sri; Widodo, Nashi; Yurina, Valentina (Science and Technology Indonesia, 2026)
The COVID-19 vaccine is one of the most important approaches for preventing SARS-CoV-2 virus transmission and spread. Oral vaccines are a promising option for preventing SARS-CoV-2 infection because it can activate both the mucosal and cellular immune systems. Previous research has shown that administering oral and intranasal vaccines can induce an immune response in mice. The effectiveness of the SARS-CoV-2 oral vaccine was evaluated in this study by combining spike protein with a carrier of food-grade recombinant Lactococcus lactis bacteria and a retinoic acid adjuvant. Mice were divided into three groups: a negative control (no treatment), a positive control (L. lactis recombinant), and a third group (L. lactis recombinant plus 300 μg retinoic acid). The vaccines were given three times, with a three-week interval between each. The serum levels of IgG, IgA, and IgE were determined using the ELISA method at the end of the study. CD4 and CD8 cellswere detected using immunofluorescence. While not statistically significant, the results showed that the retinoic acid groups had the highest anti-spike antibody levels of the three groups. In comparison to the control group, CD4 and CD8 cells increased in the spleens of mice given retinoic acid. There was no difference in temperature or IgE levels between vaccinated and non-vaccinated mice, indicating that the vaccine caused no allergic reaction. This study’s findings suggest that retinoic acid adjuvant can stimulate the cellular and humoral immune system.